Sleep quality in elite sport: measurement, management and performance - Gupta, L. (Loughborough University, 2020)
Little research to date, has explored sleep `quality`-sport interactions within the sport science and medicine literature and, as a result, information on insomnia symptomatology and its implications for sports performance among elite athletes remains unexplored. Broadly, the aim of the thesis was, therefore, to explore the construct of sleep quality in the context of elite sport performance. The first chapter systematised the literature on sleep quality among elite athletic populations and found that levels of poor sleep quality and insomnia symptomatology were generally high. The most influential source of sleep disturbance identified in the systematic review was competitions, with the literature further identifying nights immediately prior to competitions as characterised by longer sleep latencies. Because sleep is repeatedly challenged in elite sport, and night-time sleep loss is likely among athletes, the ability to compensate through daytime napping takes on a special importance. The finding in Chapter 3, however, found napping was unrelated to night-time sleep quality and introduced the possibility that napping in elite sport may, under some circumstances, be less related to homeostatic sleep need, and more related to the construct of `sleepability` (a capacity to nap on demand that is only weakly related to homeostatic sleep pressure). Again, the construct of arousal is relevant, since an ability to nap `on demand` requires also an ability to effectively manage the arousal mechanisms which promote daytime wakefulness. These assumptions were confirmed in Chapter 4, which also supplied evidence for the influence of arousal mechanisms in predicting first night effects in elite athletes. Correlations between sleep latency and Ford Insomnia Response Test (FIRST) scores (which are presumed to reflect a propensity for hyperarousal) for the adaptation trial suggest that hyperarousal may identify those athletes whose sleep is most influenced by first-night effects. Two arousal-related aspects of athlete sleep management were then addressed. In Chapter 5 the utility of the FIRST measurements was tested in a simulated Olympic tournament, where it was found that FIRST scores predicted both levels of sleep disturbance, and levels of sleep rebound. And finally, given the pervasive influence of arousal mechanisms on athlete sleep quality, Chapters 6 and 7 focussed on the delivery of sleep management programmes which, importantly, emphasised strategies to combat and manage pre-sleep arousal. That the programme reduced Dysfunctional Beliefs and Attitudes about Sleep (DBAS) scores and increased the utility of cognitive-behavioural techniques in the pilot study (Chapter 6) offers evidence for the successful transfer of `de-arousal` strategies. The acceptance of the sleep management programme during a period of competition (Chapter 7) further supports the relevance of cognitive-behavioural techniques, however modest utility and efficacy suggests further modification may be required in the context of elite competition. It is a reasonable overall conclusion from this programme of research that the systematic assessment and control of arousal-related mechanisms can improve the ability of sport management to predict and protect sleep outcomes among elite athletes.